Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/adpr.202000199
|View full text |Cite
|
Sign up to set email alerts
|

Black‐to‐Transmissive Electrochromism in π‐Conjugated Polymer‐Based Materials and Devices

Abstract: Electrochromic (EC) materials can exhibit reversible changes in their light absorption properties within the entire electromagnetic spectrum via redox reactions induced by the application of a low voltage on the order of a fraction of a volt to a few volts, holding great potential in many commercial applications, including smart windows, rear‐view mirrors, protective eyewear, and electronic paper. Of all EC materials, black EC materials, especially those that can reversibly switch between black and transmissiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…3,4-propylenedioxythiophene (PRODOT) including polymers generally show a high transparency in their oxidized states. [87,88] PRODOT derivatives were used as a co-monomer in a couple of studies. [89,90] Kuo et al reported four copolymers including bis-(4-(Ncarbazolyl)phenyl)-phenylphosphine oxide) (39) and 3,4-propylenedioxy (PRODOT) derivatives; 39-co-ProD-Me2, 39-co-ProD-Et2, 39-co-ProD-Bz2, and 39-co-ProD (Scheme 11).…”
Section: The Copolymer Films Of Push-pull Conjugated Systems With Oth...mentioning
confidence: 99%
“…3,4-propylenedioxythiophene (PRODOT) including polymers generally show a high transparency in their oxidized states. [87,88] PRODOT derivatives were used as a co-monomer in a couple of studies. [89,90] Kuo et al reported four copolymers including bis-(4-(Ncarbazolyl)phenyl)-phenylphosphine oxide) (39) and 3,4-propylenedioxy (PRODOT) derivatives; 39-co-ProD-Me2, 39-co-ProD-Et2, 39-co-ProD-Bz2, and 39-co-ProD (Scheme 11).…”
Section: The Copolymer Films Of Push-pull Conjugated Systems With Oth...mentioning
confidence: 99%
“…Various kinds of materials have been considered for EFC applications, such as organic small molecules, lanthanide-based complexes, aryl amine-appended conjugated polymers, inorganic crystals, and polymeric gels. , Meanwhile, a wide range of materials, including transition metal oxides, small organic molecules and conjugated polymers, transition metal complexes and polymers, organic–inorganic hybrid nanostructures, and plasmonic nanocrystals, exhibit variable electrochromism. However, to realize a unified EC/EFC device, material design is critical so that the chromophore can modify its optical fluorescence, in line with its redox state, and alter its absorption spectra to produce a distinct hue. According to previous literature reviews, most of the reported EC/EFC active molecules are small organic molecules such as photoredox-active thiophene or TPA derivatives, hydrogels of substituted thiazolothiazole derivatives, and carboxylic acid-substituted terpyridine. Wang et al introduced an interesting approach for creating dual EC/EFC functionality in a device composed of WO 3 /FTO and copper nanocluster/FTO, where WO 3 served as an EC layer and the copper nanocluster provided photoinduced luminescence .…”
Section: Introductionmentioning
confidence: 99%
“…This kind of electrochromic polymer is a special group of polymers because they absorb the whole visible region of the optical spectrum. [53][54][55][56][57] Color adjustment for conjugated polymers can be achieved by modifying the existing chemical structures with different substitutions or by copolymerization of different chemical units. [54] Copolymerization is a very important method to enhance the color palette and to get lower band gap.…”
Section: Introductionmentioning
confidence: 99%
“…Another challenging subject related to conjugated polymers is to obtain black to transmissive electrochromic polymer. This kind of electrochromic polymer is a special group of polymers because they absorb the whole visible region of the optical spectrum [53–57] . Color adjustment for conjugated polymers can be achieved by modifying the existing chemical structures with different substitutions or by copolymerization of different chemical units [54] .…”
Section: Introductionmentioning
confidence: 99%